THE PERCEPTION AND THE ORIGINS OF THE U. S. SOUTH CHINA SEA POLICY DURING THE EVENTS HAPPENED IN THE REGION BEFORE THE COLDWAR - Jinbo, Liu (PEOPLE: International Journal of Social Sciences, 2024)
The South China Sea policy of the United States after World War II was formed by the United States’ perception of the three events in the South China Sea before the Cold War. After events such as France’s occupation of the nine small islands in the South China Sea, Japan’s occupation of the South China Sea, and the struggle against Japan during the Pacific War, the United States has continuously deepened its understanding of the South China Sea and increasingly valued its important value. With Japan's gradual retreat in the later stages of World War II, the United States gradually gained control of the South China Sea and took a dominant position in the South China Sea dispute. With the continuous deepening of the United States' understanding of the South China Sea and the changes in its identity, status, and interests in the South China Sea region, the U.S. South China Sea policy has gradually taken shape.